X-ray diagnostics of gunshot wounds of main vessels of the limbs: theoretical analysis - Rudenko, Mykola (ScienceRise: Medical Science, 2023)
The analysis of damage to the main vessels of the limbs was considered for the formation of further organizational and tactical instructions for the provision of emergency medical care at the stages of evacuation of the injured to specialized wartime departments. It was determined that with the help of MSCT-angiography, signs of damage to main vessels can be accurately diagnosed, and additional information about damage to bone structures, neighbouring organs and tissues can be obtained. It is emphasized that MSCT is an effective and accurate method in the assessment of clinically significant arterial injuries of the lower extremities in case of gunshot injury. It was noted that timely diagnosis of vessels gunshot wounds can contribute to the preservation of the functionality of the limbs and the life of patients, reducing the risk of bleeding, infections and other complications. It was noted that the correct medical decisions, in particular, the correct diagnosis of gunshot injuries to blood vessels will help doctors make informed decisions regarding emergency surgical care, the choice of treatment methods and preoperative preparation. The aim. The aim of the work is the theoretical substantiation of gunshot injuries of the main vessels of the limbs and the definition of practical diagnostic methods. Materials and methods: analysis of theoretical sources, comparison, induction of isolated analytical data. The study was conducted based on the database of the State institution "National Institute of Cardiovascular Surgery named after M. M. Amosov of the National Academy of Medical Sciences of Ukraine". Results. It was determined that with the help of MSCT-angiography, signs of damage to main vessels can be accurately diagnosed, and additional information about damage to bone structures, neighboring organs and tissues can be obtained. Conclusions. Radiological diagnosis of gunshot injuries of the main vessels of the limbs demonstrates the importance of using radiological diagnostics in the detection and analysis of vascular injuries in gunshot injuries of the extremities. The study confirms the high efficiency of this method, its accuracy and reliability in determining the nature of damage. In addition, radiological diagnostics allows timely and accurate determination of the extent and nature of injuries, which is important for making informed clinical decisions and providing adequate medical care to the injured